Strategic Planning of Information Systems Using IT Balanced Scorecards on KSU Talenta - Yizreel Ratu Kaho; Andeka Rocky Tanaamah (Universitas Bina Darma, 2022)
Information Systems Strategic Planning is one of the determining aspects for companies in achieving goals in this digital era. One type of business that requires Information System Strategic Planning is businesses that interact directly with customers or customers related to improving services. Talenta Savings Cooperative (KSU) is one type of business that needs it, this is because information technology can improve the quality and quality of services provided to customers so that the company is ready to compete in the era of the industrial revolution 4.0. Most of the service processes at KSU Talenta are still using manual techniques. This research is qualitatively descriptive where data collection uses observation techniques, interviews, and documentation. While the method of discussing strategic planning of information systems using IT Balanced Scorecard, by conducting assessments on 4 (four) perspectives, namely, user orientation perspective, company contribution, operational improvement, and future orientation. To clarify the comparison between real conditions in the company and the ideal condition of information systems, the author also describes it using the Gap Analysis method. The result achieved is the availability of information system application series suggestions at each level of management. This strategic planning is also expected to be able to answer every need of the company in achieving existing goals.